MERCURY CONCENTRATION IN MARGIN SOIL OF THE MADEIRA RIVER - Déborah Pereira Linhares; Joiada Moreira da Silva; Tatiane Rodrigues Lima; Ronaldo Cavalcante de Oliveira; João Paulo de Oliveira Gomes; Wanderley Rodrigues Bastos; Ene Glória da Silveira (Sociedade & Natureza)
The extraction of gold in the Amazon, since 1970, has grown fast from a politic that was resulted in the creation of gold extraction reserves in this region. In the Madeira River the gold exploration is noticeable because of the deposition of mercury in the environment. This metal is toxic and it resists to degradation process, transforming itself chemically, till it gets to its organic form, known as very toxic. Its extensive usage in the gold recover has caused impacts to the environment and consequently to the population, according to studies already done. This study has as its goal to value the pollution by Hg in soils and the variation according to soil fractions. The soils were collected by profiles in 10 areas in the Madeira River. The determination of organic matter was done, according (BRASIL, 1999).To Hg determination it was selected the fraction <200 mesh (<74ım), analyzed by atomic absorption spectrophotometer coupled vapor cold generation (Bastos et. al, 1998). Soils of the kind Latosols and hydromorphic were identified. The Latosols presented from 288 to 641g.Kg-1 of clay and from 266 to 111 g.Kg-1 of thin send, from the horizon A1 (superficial) to B2 (sub-superficial). The increase of values of clay makes the function of organic matter in the superficial horizon better (from 20,2 to 19.0 %). The Hg concentration in these horizons varies from 25,5 to 641,4 ıg.Kg-1in the superficial horizon. The hydromorphic, especially, the Fluvic Neosols, present thin area, 396 to 57 g.Kg-1 and clay from 254 to 654 g.Kg-1 from A1 to A2. The horizon A2 presents 467 g.Kg-1 of silt, 13,6 % of OM and 147,31 ıgHg.Kg-1.Among the soils groups of the studied area, it is noticed more Hg concentration with the increase of values of silt and clay, that consequently presents more tenor of OM, and that subsidizes the organic mercury forming.